2007
DOI: 10.1016/j.euje.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy (left ventricular ballooning syndrome) induced during dobutamine stress echocardiography

Abstract: A 75-year-old woman presented with left ventricular apical ballooning syndrome mimicking acute anterior myocardial infarction. She had a long history of chest tightness and was undergoing a contrast stress echocardiogram because of frequent re-admissions with chest pain, all with normal ECGs and troponins. A standard dobutamine/atropine protocol had been used. The patient developed central crushing chest pain, marked ST elevation, transient slowing of heart rate and left ventricular apical ballooning. She was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…Mechanism of dobutamine induced wall motion abnormality in the absence of obstructive epicardial disease is unclear. Several theories have been postulated including multivessel coronary vasospasm, severe systemic hypertension, systolic anterior motion leading to mitral regurgitation and dynamic intracavity pressure gradient secondary to left ventricular outflow tract obstruction or mid cavity obstruction (4,5). In a systematic review, 90% of study population had hypertension, hyperlipidemia and smoking as predisposing risk factors (6).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of dobutamine induced wall motion abnormality in the absence of obstructive epicardial disease is unclear. Several theories have been postulated including multivessel coronary vasospasm, severe systemic hypertension, systolic anterior motion leading to mitral regurgitation and dynamic intracavity pressure gradient secondary to left ventricular outflow tract obstruction or mid cavity obstruction (4,5). In a systematic review, 90% of study population had hypertension, hyperlipidemia and smoking as predisposing risk factors (6).…”
Section: Discussionmentioning
confidence: 99%
“…Silberbauer et al [47] described a 75-year-old woman with higher levels of anxiety having a classic takotsubo-like apical ballooning during regular dobutamine-atropine stress echocardiography. In this case, apical ballooning was reversible, and troponin I and echocardiography changes were present associated with classic chest pain in a patient with normal coronaries, without the demonstration of coronary spasm [47].…”
Section: Pathophysiologymentioning
confidence: 98%
“…There is evidence of a strong relationship between TSC and acute mental or physiological stress [2]. Case studies have reported TSC occurring during dobutamine stress echocardiography (DSE) [3], [4]. However, a recent study on the effect of DSE in patients with a previous episode of TSC could not show a difference in tissue doppler imaging (TDI) variables during stress [5].…”
Section: Introductionmentioning
confidence: 99%